01 FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI DALAM BUDIDAYA CABAI BESAR DI DESA PATTIRO DECENG, KECAMATAN CAMBA, KABUPATEN MAROS - Jurnal Agribis; Arianul Haq; Abd. Asis Pata; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
Viewed from the side interest /, desire the big red pepper cultivation in south Sulawesi. is considered very good. Research purposes is to find factors influencing the interest farmers big red pepper in the Village Pattiro Deceng, Camba District, Maros Regency. This study was conducted in January to June 2018 in the Village Pattiro Deceng, Camba District, Maros Regency. The kind of research it uses secondary data and the analysis used is. multiple regression. The result that the variable, price , land , experience education had have real impact on interest farmers in the cultivation of big red pepper in the Village Pattiro Deceng, Camba District, Maros Regency.